Cooperative anti-leukemic effects of vitamin D derivatives and plant polyphenols in AML models: the role of the interplay between NRF2, AP-1, and VDR - Aitbekov, R.N.; Zhumina, A.G.; Danilenko, M.P. (Karagandy University of the name of academician E.A. Buketov, 2024)
Treatment of acute myeloid leukemia (AML) has not significantly improved in the past 40 years. The active form of vitamin D, 1.25-dihydroxyvitamin D3 (1,25D3), has strong in-vitro antileukemic effects at toxic concentrations in vivo. Several low-calcemic vitamin D analogs (VDAs) have been synthesized to reduce 1,25D3 toxicity. We have previously shown that plant polyphenolic antioxidants (PAOx) synergistically enhance the effects of 1,25D3 and VDAs at non-toxic doses. These effects were mediated by the nuclear factor (erythroidderived 2)-like 2 (Nrf2) and activator protein-1 (AP-1) transcription factors. The study aimed to 1) Characterize the combined effects of novel highly potent vascular disrupting agents with peroxisomal N(1)–acetylspermine/ spermidine oxidase on differentiation and growth of acute myeloid leukemia cells; 2) Elucidate the role of the interplay between nuclear factor erythroid 2, activator protein-1, and vitamin D receptor (VDR) in the combined antileukemic effects of vascular disrupting agents and peroxisomal N (1)–acetylspermine/spermidine oxidase. This article presents the treatment of AML with pharmaceutical plants and vitamin D. Such techniques as culture dilution (HL60, U937) and Western Blotting were used. We determined the in-vitro antileukemic effects of novel plant vitamin D2-based VDAs with removed C-19 (19-nor analogs; PRI-5201 and PRI-5202) or with a side-chain modification at C-24 (24-cis analogs; PRI-1916 and PRI-1917) on HL60, U937, and MOLM-13 human AML cells. The differentiation potency of PRI-5201 and PRI-5202 was 1-2 orders of magnitude higher than that of 1,25D2 or 1,25D3, while the 24-cis modification was almost ineffective. The 19-nor VDA/CA combinations are promising for treating AML. In vivo, testing of these combinations is in progress. We suggest that direct or indirect Nrf2-mediated up regulation of AP-1 and VDR by PAOx increases the sensitivity of AML cells to low doses of 1,25D3 or VDAs.
Keywords: acute myeloid leukemia (AML); nuclear factor (erythroid-derived 2)-like 2 (Nrf2); activator protein- 1 (AP1); polyphenolic antioxidants (PAOx); vitamin D analogs (VDAs)